INFORMATION AND EDUCATIONAL ENVIRONMENT FOR MONITORING AND FORMING A CUMULATIVE ASSESSMENT OF A STUDENT’S ACADEMIC WORK IN A SEMESTER - Kozlov, Vyacheslav; Alontseva, Elena; Guryanov, Alexander (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article discusses the use of the student's cumulative assessment system of academic progress as a valid element of e-learning in universities. Today, online learning is becoming mainstream. Training on online platforms is convenient and interesting, however, it is not acceptable for all students due to the need to conclude network contracts or lack of regulations on how to recalculate the results of online training at the university, etc. Using the cumulative system becomes the mechanism that solves the issue of e-learning at universities, including using distance learning technologies, without cooperating with the online platforms. The suggested approach is a new one. The purpose of the article is to study the electronic information and educational environment of the university to monitor the students’ progress. The recommended assessment means the cumulative assessment, which reflects the consistency of knowledge of the student as a participant in the training process. The recommended assessment is suggested by the information system and is calculated using a mathematical model that considers all types of student work. The assessment becomes the main one and should be considered during an interim assessment. The study of the recommended assessment formation uses the methods of mathematical statistics, data grouping, associative data sets, data verification, database manipulation. The authors also give an optimal strategy for storing large amounts of data based on minimizing their volume while maintaining the necessary access speed.